¿Cómo se mide el progreso en economía? - Zaratiegui Labiano, Jesús María (2012)
How do we measure progress in economics? Can theory change be interpreted as progress, and how? There are various possible answers that are not necessarily mutually exclusive; the question might be seeking the answer to several puzzles, each one of which needs to be answered differently. Perhaps the starting point should be to think about in parallel how the same task has been carried on in natural sciences, the model that inspired the birth and further development of economics all along. How it has been analyzed, understood and explained.